Hubungan beban kerja dengan tingkat stres perawat saat pandemi covid 19 di rumah sakit paru jember - Diajeng Lenggah Panuntun; Luh Titi Handayani; Sri Wahyuni Adriani (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2022)
Introduction: The COVID-19 pandemic has become a disease outbreak that has a very fast transmission rate. Nurses who work as part of the front line in prevention experience an increase in workload along with the increase in Covid 19 cases. As a result of the increased workload, nurses experience psychological disorders, one of which is stress. The purpose of this study was to identify the relationship between workload and stress levels of nurses during the Covid 19 pandemic at Jember Lung Hospital. Method: The type of research used is a type of correlation research with a cross-sectional approach with a population of 40 people and a sample of 37 people taken using Simple Random Sampling. The respondents who became the sample of the study were nurses who worked in the Covid 19 room. This research was carried out at the Jember Lung Hospital in November-December 2021 by collecting data with questionnaires. The analysis used in this study is the Spearman Rho test with a significance level of (α) 5%. Result: Based on data analysis, it was found that the majority of nurses experienced light workloads and the majority of nurses' stress levels were in the light stress category. With the Spearman Rho test, it was found that value = 0.036 so that the hypothesis was accepted, which means that there is a significant relationship between workload and nurse stress. Discussion: This research is suggested so that it can be used as motivation for nurses to be better at providing nursing care during the Covid 19 pandemic, especially the Covid 19 isolation room nurses and nurses who have worked in the Covid 19 isolation room.